PENERAPAN PEMASARAN DIGITAL PADA SWEES KOPI TIAM - Fendy Cuandra; Alexander, Alexander (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Micro, Small and Medium Enterprises or MSMEs are a sector that produces services and products that are directly connected to the community in their buying and selling activities. Swees Kopi Tiam is one of the MSMEs in Batam City which was founded in 1998 and is now located at Nagoya City Walk block B no 1. Swees operates in the food and beverage sector which is famous for its Epok-Epok Curry with 3 types of flavors, namely Chicken, Sardine , and Taro. The methods used in this service are observation and interview methods. Since the beginning of its operations, Swees has never done digital marketing, so for this service an Instagram account and menu were created that can build the partner's image in the community